Peran KUA Kecamatan Pameungpeuk dalam Sertifikasi Wakaf Tanah dikaitkan dengan Teori Mashlahah - Muhamad Osamah Fahrul Roji; Muhammad Yunus; Ilham Mujahid (UNISBA Press, 2024)
Abstract. Waqf land registration does not only include the Waqf Pledge and is completed until the issuance of the Waqf Pledge Deed, there are still additional stages that must be met to comply with the government. The purpose of completing the waqf land registration process to completion is to prevent future problems such as waqf land disputes. So that the institution that is authorized to take care of this issue is the Office of Religious Affairs (KUA) which concurrently serves as the Official of the Waqf Pledge Deed (PPAIW). With the legal basis of Law No. 41 of 2004 which emphasizes that PPAIW is obliged to submit to the BPN office to register land for waqf land that already has AIW a maximum of 7 working days after the signing of the AIW. This study aims to examine how waqf land certification in KUA Pameungpeuk District is associated with the mashlahah theory. The method used is qualitative with a normative juridical approach. The results of the analysis obtained by the researcher show that the waqf land certification process in the KUA of Pameungpeuk District has not fully complied with the provisions of the applicable laws. Then when associated with the concept of mashlahah, this land waqf certification is included in the category of mashlahah mu'tabarah with the level of hajiyah, which is an important thing to do to avoid a madharatan. Abstrak. Pencatatan tanah wakaf tidak hanya mencakup Ikrar Wakaf dan selesai hingga terbit Akta Ikrar Wakaf, masih ada tahapan tambahan yang harus dipenuhi untuk mematuhi pemerintah. Tujuan dari menyelesaikan proses pencatatan tanah wakaf hingga selesai adalah untuk mencegah masalah yang akan datang seperti sengketa tanah wakaf. Sehingga lembaga yang berwenang dalam mengurus persoalan ini adalah Kantor Urusan Agama (KUA) yang merangkap sebagai Pejabat Pembuat Akta Ikrar Wakaf (PPAIW). Dengan dasar hukum Undang-Undang No. 41 Tahun 2004 yang menegaskan bahwa PPAIW wajib menyampaikan kepada kantor BPN guna melakukan pendaftaran tanah terhadap tanah wakaf yang telah memiliki AIW maksimal 7 hari kerja setelah penandatanganan AIW. Penelitian ini bertujuan untuk menelaah bagaimana sertifikasi tanah wakaf di KUA Kecamatan Pameungpeuk dikaitkan dengan teori mashlahah. Metode yang digunakan adalah kualitatif dengan pendekatan yuridis normatif. Hasil analisis yang peneliti peroleh bahwa proses sertifikasi tanah wakaf di KUA Kecamatan Pameungpeuk belum sepenuhnya mematuhi ketentuan Perundang-Undangan yang berlaku. Kemudian apabila dikaitkan dengan konsep mashlahah, sertifikasi wakaf tanah ini termasuk kategori mashlahah mu’tabarah dengan tingkatan hajiyah, yaitu suatu hal yang penting untuk dilakukan untuk menghindari sebuah kemadharatan.